Enhancing Public Service Access for Vulnerable Groups Through the Pentahelix-Based Inclusive Village Model - Achmad Hariri; Holly Ichda Wahyuni; Agus Supriyo (Universitas Lampung, 2025)
The Pentahelix approach is essential for enhancing access to and the quality of public services for vulnerable groups in Desa Karduluk, Sumenep. By fostering collaboration among government, academia, businesses, communities, and media, this model aims to create fairer, more effective, and sustainable services. This study employs a juridical-empirical method to assess the implementation of the Pentahelix approach in developing an inclusive village. The findings highlight its potential but also reveal challenges, including the absence of village-level regulations and limited private sector involvement. Academia, particularly IAIN Madura, has contributed through Tri dharma activities, albeit on a limited scale. Local businesses play a minor role, requiring training and market access support. Community groups, such as Parjughe and Pemuda Peduli, demonstrate concern for vulnerable populations but have not specifically addressed disability issues. While local media like kimpragaan.com have been active, broader media engagement remains limited.